Adherence to Physical Activity Among Older Adults Using a Geographic Information System: Korean National Health and Nutrition Examinations Survey IV - Hye-A Yeom, PhD, RN; Dukyoo Jung, PhD, RN; Mona Choi, PhD, RN (Elsevier, 2011)
The purpose of this study was to examine the adherence to physical activity (PA) among older adults in Korea using data from the Fourth Korean National Health and Nutrition Examination Survey (KNHANESIV), and to illustrate geographic variations in PA using Geographic Information Systems (GIS). Methods: A secondary analysis of the KNHANES IV data from 2007 to 2008 was used for this study. Participants of the study included 2,241 older adults over the age of 65. Estimates on adherence to PA were obtained for vigorous, moderate, walking, strengthening, and stretching activities. All estimates were weighted to represent Korean population. The association between participants' characteristics and PA was analyzed using Wald chi-square test. Maps depicting regional variations in PA were created using GIS software. Results: Adherence to PA among Korean older adults who met national recommendations during the period of year 2007-2008 was about 9% in vigorous activity, 10% in moderate activity, and 48% in walking. The most common type of PA was walking. A higher level of PA was associated with male gender, younger age, high level of income and education, and living with family. Conclusion: The majority of older adults did not meet the national PA recommendations, suggesting that consistent surveillance and intervention for PA in the geriatric population are needed in the future. Maps generated using GIS visually showed regional differences in PA among the study participants.